Analysis of Local Wisdom of Mendale Village Fisherman Communities in the Fishing Process - Puspitawati Puspitawati; Ivan Loo Pei Ze (Taiwan) (JURNAL GEOGRAFI, 2023)
Local knowledge is knowledge owned by a community in the form of information that is people's knowledge. As a country with diverse cultures, Indonesia has a variety of local knowledge which has become an icon of the community, used in maintaining natural conditions and survival. One of the community's local knowledge areas is the process of fishing in the Gayo community. The Gayo ethnic group is a native of Central Aceh District, located in the Gayo highlands. Local knowledge possessed by the community is inseparable from global influences that continue to grow. Global forces will shape culture, modify value systems, and affect social identity. This research was conducted in Mendale Village, Kebayakan District, Central Aceh District. This study aims to analyze local and global knowledge and find out the acculturation of people in fishing. The research method used is a qualitative method with a new ethnographic approach. Data collection techniques are interviews, observation, and documentation studies. The results of interviews and observations were analyzed thematically and grouped under the same theme. Each theme is discussed in detail and then interpreted to obtain data that can provide answers to research problems. The research results show that local knowledge of fishing is a culture passed down from generation to generation. Local fishing knowledge cannot be applied in all catches, only used in fishing in the lake. Existing local knowledge is mixed with global knowledge so that local knowledge of fishing is not the same as the culture left by fishermen in the past.Keywords: Local Knowledge, Gayo, Community Fishing, Acculturation